2018
DOI: 10.1111/php.12848
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Cascades Activated by UVB in Human Melanocytes Lead to the Increased Expression of Melanocyte Receptors, Endothelin B Receptor and c‐KIT

Abstract: A single exposure of normal human melanocytes (NHMs) to ultraviolet B (UVB) radiation induces a distinct increase in the expression of c-KIT and endothelin B receptor (EDNRB) and upregulates the expression of microphthalmia-associated transcription factor (MITF). In this review, we clarify the signaling mechanisms by which UVB stimulates the expression of MITF in NHMs, thus leading to upregulation of those two important melanogenic receptors. The increased expression of MITF in UVB-exposed NHMs is accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
0
17
0
3
Order By: Relevance
“…Activation of the MC microphthalmia‐associated transcription factor (MITF) in response to secretion of KC‐derived factors (e.g., alpha MC‐stimulating hormone [α–MSH], kit ligand [KITL], endothelin 1 [END‐1]) following UV exposure results in upregulation of melanin‐producing enzymes (including TYRP1, tyrosinase‐related protein 1), and melanin production and secretion (Nguyen & Fisher, ; Serre et al, ). UV exposure also initiates signaling cascades in both KCs and MCs, resulting in secretion of cytokines and chemokines including interleukins (IL1, IL3, IL6, and IL8), interferon (IFN‐γ), granulocyte‐colony stimulating factor (G‐CSF), and tumor necrosis factor α (TNF‐α) (Schwarz & Luger, ; Terazawa & Imokawa, ; Yoshizumi et al, ), which control processes involving cross talk between cells such as the tanning response within the KC:MC unit. Lengthened dendrites and increased dendrite branching in response to UV light increase MC interactions with KCs to facilitate melanin transfer (López et al, ; Weiner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the MC microphthalmia‐associated transcription factor (MITF) in response to secretion of KC‐derived factors (e.g., alpha MC‐stimulating hormone [α–MSH], kit ligand [KITL], endothelin 1 [END‐1]) following UV exposure results in upregulation of melanin‐producing enzymes (including TYRP1, tyrosinase‐related protein 1), and melanin production and secretion (Nguyen & Fisher, ; Serre et al, ). UV exposure also initiates signaling cascades in both KCs and MCs, resulting in secretion of cytokines and chemokines including interleukins (IL1, IL3, IL6, and IL8), interferon (IFN‐γ), granulocyte‐colony stimulating factor (G‐CSF), and tumor necrosis factor α (TNF‐α) (Schwarz & Luger, ; Terazawa & Imokawa, ; Yoshizumi et al, ), which control processes involving cross talk between cells such as the tanning response within the KC:MC unit. Lengthened dendrites and increased dendrite branching in response to UV light increase MC interactions with KCs to facilitate melanin transfer (López et al, ; Weiner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…During these downstream cascades, further signaling factors such as CREB for MSK1 (59), NFkB (Ser276) for MSK1 (60,61) and c-Fos for CREB (62) are continuously and sequentially activated. Several functional proteins that are highly expressed in UVB-exposed human keratinocytes or human melanocytes, such as cyclooxygenase (COX)2 (50), interleukin (IL)-8 (50), transglutaminase1 (49) (in human keratinocytes), endothelin B receptor (51,63) and stem cell factor receptor c-KIT (in human melanocytes) (63, 64) utilize their characteristic and specific signaling cascades to elicit their increased gene expression.…”
Section: Effects Of Maas On Intracellular Signaling Cascades In Hdfsmentioning
confidence: 99%
“…We next determined if the increased production of SCF triggers EDNBR expression or its affinity to the EDN ligand in human melanocytes in addition to its stimulatory effect on their proliferation. Western blotting analysis revealed that SCF can stimulate the expression of EDNBR protein in cultured human melanocytes [43]. When the affinity of EDNBR to its ligand was evaluated in cultured human melanocytes using a ligand binding assay, the binding of 125 I-lableled EDN1 to EDNBR was found to be significantly increased two days after incubation with SCF [43].…”
Section: Mechanisms Of Melanocyte Activation In Solar Lentigo Basementioning
confidence: 99%
“…Western blotting analysis revealed that SCF can stimulate the expression of EDNBR protein in cultured human melanocytes [43]. When the affinity of EDNBR to its ligand was evaluated in cultured human melanocytes using a ligand binding assay, the binding of 125 I-lableled EDN1 to EDNBR was found to be significantly increased two days after incubation with SCF [43]. Taken together, these findings indicate that SCF expressed in the early phase may enhance the expression of EDNBR, which cause melanocytes to become more sensitive to the later secretion of EDN1.…”
Section: Mechanisms Of Melanocyte Activation In Solar Lentigo Basementioning
confidence: 99%
See 1 more Smart Citation